Aliansi Strategis dan Kinerja Perusahaan: Perspektif Teori Institusional - Rebi Fara Handika (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2020)
This paper discussed the company's motive to join a strategic alliance from the institutional theory point of view. The theory views that strategic alliances are considered as the medium to acquire legitimation from the environment. Such legitimation then improves the company’s competitive positions and performance. Further, we propose the framework to discuss the relationship between strategic alliances and a company’s performance. The paper proceeds as follows: in the next section, we discuss the institutional theory, the strategic alliance, and firm performance. Afterward, we develop the propositions and discuss the implications for future empirical research.